Analysis of the Decision of the State Administrative Court Number 282/G/2019/PTUN.MDN Concerning the Dismissal of the Head of Sampali Village from the Perspective of Fiqh Siyasah - Dalimunthe, Said Hasan Al-Khindawi; Firmansyah, Heri (LEGAL BRIEF, 2025)
: Provinces and regencies/cities are autonomous regions, namely a legal entity with clear territorial boundaries and have the rights, authority, and responsibility to regulate and manage their own government affairs. Village apparatus plays a role in supporting the village head to ensure the smooth administration of government, provide services needed by the community, and carry out village obligations, duties, and functions. The purpose of the research is to find out how the decision of the state administrative court Number 282/G/2019/PTUN.MDN concerns the dismissal of the head of the Sampali village hamlet from the perspective of fiqh siyasah. Research method, normative legal research. The results of the research, the dismissal of the Head of the Sampali Village Hamlet was carried out without deliberation, adequate notification, or consultation with the sub-district head, as a result of which it violated Law Number 3 of 2024 concerning Villages and Regulation of the Ministry of Home Affairs Number 67 of 2017, as a result the decision was declared null and void, and the defendant was ordered to revoke the decision, return the plaintiff to his original position, and pay court costs. According to the perspective of fiqh siyasah, this decision reflects the application of the principles of justice ('adl), deliberation (shura), and responsibility (mas'uliyyah) in governance. The act of dismissing the village head without going through a legitimate procedure not only violates state law, but also the ethics of Islamic leadership. This case is an important precedent for applying the values ??of fiqh siyasah in maintaining the welfare of the community and the integrity of the village government